2015
DOI: 10.1148/radiol.14140528
|View full text |Cite
|
Sign up to set email alerts
|

Fast Whole-Brain Three-dimensional Macromolecular Proton Fraction Mapping in Multiple Sclerosis

Abstract: ).q RSNA, 2014 Purpose:To evaluate the clinical utility of fast whole-brain macromolecular proton fraction (MPF) mapping in multiple sclerosis (MS) and compare MPF with established quantitative magnetic resonance (MR) imaging measures of tissue damage including magnetization transfer (MT) ratio and relaxation rate (R1). Materials and Methods:In this institutional review board-approved and HIPAAcompliant study, 14 healthy control participants, 18 relapsing-remitting MS (RRMS) patients, and 12 secondary progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
101
2
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 69 publications
(121 citation statements)
references
References 41 publications
15
101
2
3
Order By: Relevance
“…The MPF is a biophysical parameter describing the amount of macromolecular protons in tissues involved in cross-relaxation with free water showed promising clinical results in adult brain studies 11,12 and has been histologically validated as an accurate quantitative tool for measuring demyelination. 10 The single-point technique 4 also allowed designing an ultrafast MPF mapping protocol for nonbrain applications.…”
mentioning
confidence: 99%
“…The MPF is a biophysical parameter describing the amount of macromolecular protons in tissues involved in cross-relaxation with free water showed promising clinical results in adult brain studies 11,12 and has been histologically validated as an accurate quantitative tool for measuring demyelination. 10 The single-point technique 4 also allowed designing an ultrafast MPF mapping protocol for nonbrain applications.…”
mentioning
confidence: 99%
“…Detailed characteristics of the study population can be found elsewhere [4]. Caudate nucleus, putamen, globus pallidus and substantia nigra were outlined on MPF maps.…”
Section: Methodsmentioning
confidence: 99%
“…At present it was obvious that gray matter damage which was poorly detectable using conventional MRI method occurred at the first stage of MS and correlated with clinical symptoms (both motor and cognitive) [2]- [4] Subcortical gray matter involvement in MS pathology was also observed [2], [5]but still need to be studied. In our research, basal ganglia demyelination in MS patients was evaluated using fast mapping of macromolecular proton fraction (MPF).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations